DNA Sequence Analysis of the PorB Protein of Nonserotypeable Serogroup C ET-15 Meningococci Suggests a Potential Mutational Hot Spot on Their Serotype Antigens - Law, Dennis K. S. (American Society for Microbiology, 2004)
The nucleotide sequences of the PorB proteins from 28 nonserotypeable serogroup C ET-15 meningococci recovered from invasive meningococcal disease cases were determined. PCR amplification of the porB genes responsible for encoding the serotype antigen was used for DNA sequence determination and identification of the nature of the serotype antigen. DNA sequencing revealed that three strains were of serotype 2a, and of the remaining 25 strains, 20 were found to have an identical single point mutation in the region of the VR3 gene, which encodes surface-exposed loop VI, where the serotype 2a epitope resides. This nonsynonymous mutation was confirmed by synthetic peptide immunochemical analysis to confer new serospecificity to these serotype 2a mutants. This finding of a potential novel mutational hot spot on the PorB proteins of meningococci may have implications for pathogenesis and vaccine development.